High-quality endoscope reprocessing decreases endoscope contamination. (October 2018) - Decristoforo, P.; Kaltseis, J.; Fritz, A.; Edlinger, M.; Posch, W.; Wilflingseder, D.; Lass-Flörl, C.; Orth-Höller, D.; ,
Abstract: Objectives: Several outbreaks of severe infections due to contamination of gastrointestinal (GI) endoscopes, mainly duodenoscopes, have been described. The rate of microbial endoscope contamination varies dramatically in literature. The aim of this multicentre prospective study was to evaluate the hygiene quality of endoscopes and automated endoscope reprocessors (AERs) in Tyrol/Austria. Methods: In 2015 and 2016, a total of 463 GI endoscopes and 105 AERs from 29 endoscopy centres were analysed by a routine (R) and a combined routine and advanced (CRA) sampling procedure and investigated for microbial contamination by culture-based and molecular-based analyses. Results: The contamination rate of GI endoscopes was 1.3%–4.6% according to the national guideline, suggesting that 1.3–4.6 patients out of 100 could have had contacts with hygiene-relevant microorganisms through an endoscopic intervention. Comparison of R and CRA sampling showed 1.8% of R versus 4.6% of CRA failing the acceptance criteria in phase I and 1.3% of R versus 3.0% of CRA samples failing in phase II. The most commonly identified indicator organism was Pseudomonas spp., mainly Pseudomonas oleovorans . None of the tested viruses were detected in 40 samples. While AERs in phase I failed ( n = 9, 17.6%) mainly due to technical faults, phase II revealed lapses ( n = 6, 11.5%) only on account of microbial contamination of the last rinsing water, mainly with Pseudomonas spp. Conclusions: In the present study the contamination rate of endoscopes was low compared with results from other European countries, possibly due to the high quality of endoscope reprocessing, drying and storage.